Judo mixed team event match outcome and the Judo World Ranking List - Gustavo Goulart Braga Maçaneiro; Andrés Pardo-Ginés; Emerson Franchini (Universidad de León, 2021)
The Judo World Ranking List has been used to assess its predictive power regarding athletic performance. The aim of this study was to check if the ranking difference among athletes in the individual rankings could be used as a predictor for the outcome of mixed teams judo competition. We sought to verify the association between the variable "rank difference" and the probability of the higher-ranked athlete winning against that lower-ranked. This heterogeneity between athletes is a major factor in increasing or decreasing the team's chances of winning. The higher ranked athlete's defeat seems to have a significant negative effect on his/her teammates in subsequent bouts. These findings imply that future studies on mixed teams judo competitions should consider individual ranking differences among athletes as a predictor of performance.